2018
DOI: 10.3390/v10080419
|View full text |Cite
|
Sign up to set email alerts
|

Swine Influenza Virus Induces RIPK1/DRP1-Mediated Interleukin-1 Beta Production

Abstract: Nucleotide-binding domain and leucine-rich repeat-containing protein 3 (NLRP3) inflammasome plays a pivotal role in modulating lung inflammation in response to the influenza A virus infection. We previously showed that the swine influenza virus (SIV) infection induced NLRP3 inflammasome-mediated IL-1β production in primary porcine alveolar macrophages (PAMs), and we were interested in examining the upstream signaling events that are involved in this process. Here, we report that the SIV-infection led to dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 61 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…Similarly, Park et al also reported mitochondrial fission mediated by the RIPK1-DRP1 signaling axis leads to NLRP3 inflammasome dependent IL-1β secretion from swine influenza virus-infected macrophages. The secretion of IL-1β from infected macrophages was found to be contingent upon accelerated mtROS production [ 168 ]. Conversely, the IFN-induced 2’,5’-oligoadenylate synthetase (OAS)/ribonuclease L (RNase L) system is also associated with NLRP3 activation as the release of IL-1β is minimal in IAV-infected RNase L-deficient BMDCs.…”
Section: Nod- Lrr- and Pyrin Domain-containing Protein 3 (Nlrp3)mentioning
confidence: 99%
“…Similarly, Park et al also reported mitochondrial fission mediated by the RIPK1-DRP1 signaling axis leads to NLRP3 inflammasome dependent IL-1β secretion from swine influenza virus-infected macrophages. The secretion of IL-1β from infected macrophages was found to be contingent upon accelerated mtROS production [ 168 ]. Conversely, the IFN-induced 2’,5’-oligoadenylate synthetase (OAS)/ribonuclease L (RNase L) system is also associated with NLRP3 activation as the release of IL-1β is minimal in IAV-infected RNase L-deficient BMDCs.…”
Section: Nod- Lrr- and Pyrin Domain-containing Protein 3 (Nlrp3)mentioning
confidence: 99%
“…Swine IV (SIV) infection resulted in NLRP3 inflammasome activation, leading to IL-1β production in primary porcine alveolar macrophages (PAMs) [122]. Furthermore, upon SIV infection of PAMs, mitochondrial fission occurred through the RIPK1/DRP1 axis, which acted on the NLRP3 inflammasome-regulated production of IL-1β [123]. IAV produced endogenous ROS via NOX2-containing NOXs and mitochondria, to circumvent anti-IAV responses.…”
Section: Potential Interaction With Inflammasomesmentioning
confidence: 99%
“…DRP1 is activated by the RIPK1–RIPK3 complex, formed in cells infected with RNA viruses, and translocates to the mitochondria to promote NLRP3 inflammasome activation, which establishes the role of the RIPK1–RIPK3–DRP1 pathway in NLRP3 inflammasome activation [134]. In line with this finding, swine influenza virus-infection leads to NLRP3 inflammasome activation and IL-1β secretion in porcine alveolar macrophages in an RIPK1/DRP1 complex-dependent manner, which indicates the critical role of the RIPK1/DRP1 signaling axis in modulating porcine NLRP3 inflammasome activation [179]. The RIPK1/RIPK3/DRP1 pathway has also been proposed to contribute to the activation of NLRP3 inflammasome in the subarachnoid hemorrhage induction animal model [180].…”
Section: Cell Death Regulators Associated With the Inflammasomementioning
confidence: 80%